Sunscreen composite powder with antibacterial function
The g-C3N4/iron-silver co-doped hydroxyapatite composite powder formed by Fe3+ and Ag+ ion doping and g-C3N4 complex is solved, and the problem of insufficient ultraviolet absorption and antibacterial performance in the prior art is achieved. The strong absorption and antibacterial effect of light in the wavelength range of 220-430nm and maintain stability in sunlight. It is suitable as a cosmetics and clothing additive for sun protection.
Patent Information
- Application Number
- CN202411355480.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
AI Technical Summary
The existing metal ion-doped hydroxyapatite has insufficient performance in terms of ultraviolet absorption and antibacterial functions, and the introduced rare earth elements are potentially harmful to the human body. Physical sunscreens are prone to degeneration in sunlight, and lack both efficient ultraviolet absorption and antibacterial. Sunscreen complex.
By doping Fe3+ and Ag+ ions into hydroxyapatite and recombining in situ with graphitized carbon nitride (g-C3N4) to form a g-C3N4/ferrosilver co-doped hydroxyapatite composite powder, optimized Its component ratio is to improve ultraviolet absorption and antibacterial properties, while inhibiting the photocatalytic activity of g-C3N4, improving the color of the material close to the natural skin tone.
It has achieved strong absorption of light in the wavelength range of 220-430nm, has good antibacterial effect, has a color close to natural skin tone, and has good stability in sunlight, and is suitable as a cosmetics and clothing additive for sun protection.
Smart Images

Figure CN119214944A_ABST
Abstract
Description
Technical Field
[0001] The invention provides a composite powder for sunscreen with antibacterial function, and the material belongs to the field of antibacterial and sunscreen functional powders. Background Art
[0002] Ultraviolet rays in sunlight are one of its important components, and its wavelengths can be divided into three bands: UVA (320-400nm), UVB (280-320nm), and UVC (200-280nm). UVA can penetrate the skin with ultraviolet radiation, causing problems such as sagging and aging of the skin. Excessive exposure to UVB can cause skin pigmentation, stimulate the production of melanocytes, lead to the formation of melanin, produce sun spots and age spots, and cause a series of skin problems. Even if the ozone layer is depleted, some UVC can reach the earth's surface and cause damage to the skin. It is reported that the three main types of skin cancer, including basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and melanoma, are all caused by ultraviolet radiation. Sunscreen, as a common and effective sunscreen method, can shield ultraviolet rays and protect the skin.
[0003] Currently, sunscreens are mainly divided into chemical sunscreens and physical sunscreens. Many chemical sunscreens can penetrate into the skin, causing photoallergy, phototoxicity and skin irritation, and the sunscreen effect will decay as the chemical reaction proceeds. For these reasons, physical sunscreens are currently a better choice.
[0004] Hydroxyapatite [Ca 10 (PO4)6(OH)2] complies with complete epidermal and systemic tolerance, and can be modified to obtain ultraviolet absorption function for use in physical sunscreens. It is highly effective in protecting the skin from sunlight UV rays, and this effectiveness is greater than the effectiveness shown by zinc oxide and titanium dioxide. In addition, a surprising whitening effect was observed on the skin after application. The corresponding functional design of its ion doping can make the hydroxyapatite powder have more functions. Therefore, the modification of hydroxyapatite has gradually become a hot topic in the field of sunscreen. Patent CN 114681615A prepared an iron ion-doped hydroxyapatite, which obtained good osteogenic ability and certain antibacterial properties, but it did not involve relevant information on ultraviolet absorption. Patent CN 112062114 A provides a trivalent manganese ion-doped hydroxyapatite, which gives hydroxyapatite high catalytic efficiency and certain antibacterial functions, but does not consider the ability to absorb ultraviolet light. Paduraru AV et al. used Ce by coprecipitation method 3+ and Ce 4+ Substituting Ca in hydroxyapatite 2+(Paduraru AV, Musuc AM, Oprea OC, et al. Synthesis and Characterization of Photoluminescent Ce(III)and Ce(IV)Substituted Hydroxyapatite Nanomaterials by Co-Precipitation Method: Cytotoxicity and Biocompatibility Evaluation[J]. Nanomaterials, 2021, 11(8): 15.), significantly improved the ultraviolet absorption function of hydroxyapatite, but did not consider the antibacterial function of the material. CN 117208871A prepared a trivalent cerium ion, silver ion, and zinc ion doped hydroxyapatite powder, which has both ultraviolet absorption and antibacterial functions, but it introduces rare earth elements that are potentially harmful to the human body, and has insufficient light absorption capacity in the wavelength range of 310-430nm. Therefore, the application performance of metal ion-doped hydroxyapatite can still be further optimized.
[0005] Graphitized carbon nitride (g-C3N4) two-dimensional nanosheets are inorganic polymer semiconductors and two-dimensional sheet structures. They have good mechanical strength and good absorption capacity for ultraviolet light less than 400nm, but their strong photocatalytic activity may cause the sunscreen to denature under sunlight. Patent CN 114404314A discloses a sunscreen compound and its preparation method. The sunscreen compound is formed by g-C3N4 and a zinc zeolite imidazolate framework ZIF-8 loaded thereon. The compound is added to a cosmetic base material at a mass ratio of 10% of the total mass, and a strong absorption capacity is obtained in the wavelength range of 210-500nm, but the antibacterial function that should be possessed when used as a sunscreen is not considered.
[0006] Therefore, the present invention provides a g-C3N4 / iron-silver co-doped hydroxyapatite composite powder, which has the characteristics of strong absorption in the wavelength range of 220-430nm, good antibacterial performance and chromaticity close to natural skin color.
[0007] First of all, the reasonable matching of the two ion components is the key to ensure that the material has high efficiency in UV absorption and antibacterial function. We used the precipitation method to convert Fe 3+ and Ag + Replace part of Ca in hydroxyapatite 2+ , Ag + Endows hydroxyapatite with the main antibacterial function; Fe 3+The hydroxyapatite is endowed with the main ultraviolet absorption function and has partial antibacterial function. Secondly, the appropriate doping amount of the two ion components is another key to ensure the multifunctionality of the material. If the doping amount is too low, it is difficult to make the material have the corresponding functionalization. If the doping amount is too high, the crystal structure of the material may be destroyed and impurities may appear.
[0008] When hydroxyapatite is doped with Fe 3+ and Ag + After in-situ compounding with g-C3N4, the photocatalytic activity of g-C3N4 itself is inhibited, reducing the possibility of denaturation and inactivation of the sunscreen under sunlight; the absorption capacity of iron-silver co-doped hydroxyapatite for light in the wavelength range of 310-430nm is enhanced; hydroxyapatite exhibits a light reddish brown color after being doped with trivalent iron ions, and the two-phase combination of the composite powder changes this defect, making its color close to the natural skin color of Asians.
[0009] The present invention is to g-C3N4 / (Ca 10-x-y Fe x Ag y The composition and proportion of )(PO4)6(OH)2 have been reasonably optimized to ensure that the material has high phase purity, low cost, and good safety, while also having the characteristics of efficient UV absorption, antibacterial function, and color close to natural skin color. It also retains the inherent effects of hydroxyapatite in thickening and moisturizing, and is suitable for use as a functional additive for sunscreen cosmetics, clothing, and parasols. Summary of the invention
[0010] The present invention provides a sunscreen composite powder with antibacterial function. The sunscreen composite powder with antibacterial function is characterized by iron-silver co-doped hydroxyapatite and g-C3N4 composite, and its chemical composition is expressed as g-C3N4 / (Ca 10-x-y Fe x Ag y )(PO4)6(OH)2, where 0.1≤x≤1, 0.1≤y≤1, and the mass ratio of g-C3N4 in the composite powder is 20% to 40% of the total mass. Part of Ca in the hydroxyapatite lattice 2+ Fe 3+ 、Ag + The g-C3N4 / iron-silver co-doped hydroxyapatite composite powder has a strong absorption effect on light in the wavelength range of 220-430nm, especially the g-C3N4 composite strengthens the light absorption of the modified hydroxyapatite in the wavelength range of 310-430nm. It has a good antibacterial effect on Staphylococcus aureus and Escherichia coli, and the color of the composite powder is close to the natural skin color of Asians.
[0011] The preparation method of the g-C3N4 / iron-silver co-doped hydroxyapatite composite powder is as follows:
[0012] (1) Weigh 10.0 g of melamine into a covered crucible, heat it to 500°C at a heating rate of 5°C / min at room temperature, calcine it in air for 4 h, take it out, cool it to room temperature, grind it manually and sieve it to collect powders smaller than 1000 mesh, then heat the powder to 500°C at a heating rate of 5°C / min at room temperature, calcine it in air for 2 h, and obtain g-C3N4 powder.
[0013] (2) 2.5-25.0 ml of 0.1 M Fe(NO3)3 solution, 1.2-12.5 ml of 0.2 M AgNO3 solution and 40.0-49.0 ml of 0.5 M Ca(NO3)2 solution were respectively weighed and mixed with 1.2 g-2.8 g g-C3N4 and ultrasonically treated for 20 min. The mixture was vigorously stirred at 95 °C on a magnetic stirring table for 1 h. Subsequently, 50.0 ml of 0.3 M NH4H2PO4 solution was added. The pH value was adjusted to 10-11 by dropping NH3·H2O. The mixture was cooled to room temperature and vigorously stirred for 1 h to obtain a mixed solution A.
[0014] (3) The mixed solution A is sealed at normal pressure to prevent the water from evaporating, and aged at 20-30°C for 24 hours.
[0015] (4) The precipitate was separated by filtration, and was washed alternately with 50.0 mL of anhydrous ethanol and 50.0 mL of deionized water, and centrifuged. The alternating washing was repeated 3 times, and the mixture was dried at 80 °C for 24 h. The mixture was then heated to 200 °C at a heating rate of 5 °C / min at room temperature, and calcined in air for 2 h to obtain g-C3N4 / iron-silver co-doped hydroxyapatite composite powder.
[0016] The beneficial effects of the present invention are as follows:
[0017] The g-C3N4 / iron-silver co-doped hydroxyapatite composite powder provided by the present invention has high phase purity, stable structure, strong absorption of light with a wavelength of 220-430nm, good antibacterial effect on Staphylococcus aureus and Escherichia coli, and has the effects of thickening and moisturizing, and the chromaticity is close to the natural skin color. The raw material source of the material is wide, the price is low, and it has the advantages of simple process and long-term storage of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is the UV-DRS spectrum of the g-C3N4 / iron-silver co-doped hydroxyapatite composite powder prepared by the present invention.
[0019] Figure 2 This is a photo of the antibacterial ring of the g-C3N4 / iron-silver co-doped hydroxyapatite composite powder prepared by the present invention. Specific implementation methods
[0020] The present invention is further described below in conjunction with the accompanying drawings and embodiments. The above description is only an embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent transformation using the contents of the present invention description and drawings, or directly or indirectly applied to other related technical fields, are also included in the patent protection scope of the present invention.
[0021] Example 1
[0022] g-C3N4 / (Ca 9.4 Fe 0.1 Ag 0.5 )(PO4)6(OH)2 (wherein the content of g-C3N4 is 20%) composite powder
[0023] 2.5 ml of 0.1 M Fe(NO3)3 solution, 6.25 ml of 0.2 M AgNO3 solution and 47.0 mL of 0.5 M Ca(NO3)2 solution were respectively taken and mixed with 1.2 g of g-C3N4 and ultrasonically treated for 20 min, and then stirred at 95 °C for 1 h. Subsequently, 50.0 mL of 0.3 M NH4H2PO4 solution was added, and the pH value was adjusted to 10-11 by dropping NH3·H2O. The mixture was stirred for 1 h at room temperature to obtain a mixed solution A. The mixed solution A was sealed at normal pressure to prevent the water from evaporating, and aged at 20-30 °C for 24 h. The precipitate was separated by filtration, and washed alternately with 50.0 mL of anhydrous ethanol and 50.0 mL of deionized water, and centrifuged. The alternating washing was repeated 3 times, and dried at 80 °C for 24 h, and then heated to 200 °C at a heating rate of 5 °C / min at room temperature, and calcined in air for 2 h to obtain g-C3N4 / (Ca 9.4 Fe 0.1 Ag 0.5 )(PO4)6(OH)2 composite powder.
[0024] Example 2
[0025] g-C3N4 / (Ca 9.4 Fe 0.1 Ag 0.5 )(PO4)6(OH)2 (wherein the content of g-C3N4 is 30%) composite powder
[0026] 2.5 ml of 0.1 M Fe(NO3)3 solution, 6.3 ml of 0.2 M AgNO3 solution and 47.0 ml of 0.5 M Ca(NO3)2 solution were respectively taken and mixed with 1.9 g of g-C3N4 and ultrasonically treated for 20 min, and then stirred at 95 °C for 1 h. Subsequently, 50.0 ml of 0.30 M NH4H2PO4 solution was added, and the pH value was adjusted to 10-11 by dropping NH3·H2O. The mixture was stirred for 1 h at room temperature to obtain a mixed solution A. The mixed solution A was sealed at normal pressure to prevent the water from evaporating, and aged at 20-30 °C for 24 h. The precipitate was separated by filtration, and washed alternately with 50 ml of anhydrous ethanol and 50 ml of deionized water, and centrifuged. The alternating washing was repeated 3 times, and dried at 80 °C for 24 h, and then heated to 200 °C at a heating rate of 5 °C / min at room temperature, and calcined in air for 2 h to obtain g-C3N4 / (Ca 9.4 Fe 0.1 Ag 0.5 )(PO4)6(OH)2 composite powder.
[0027] Example 3
[0028] g-C3N4 / (Ca 9.4 Fe 0.1 Ag 0.5 )(PO4)6(OH)2 (wherein the content of g-C3N4 is 40%) composite powder
[0029] 2.5 ml of 0.1 M Fe(NO3)3 solution, 6.3 ml of 0.2 M AgNO3 solution and 47.0 ml of 0.5 M Ca(NO3)2 solution were respectively taken and mixed with 2.8 g of g-C3N4 and ultrasonically treated for 20 min, and then stirred at 95 °C for 1 h. Subsequently, 50.0 ml of 0.3 M NH4H2PO4 solution was added, and the pH value was adjusted to 10-11 by dropping NH3·H2O. The mixture was stirred for 1 h at room temperature to obtain a mixed solution A. The mixed solution A was sealed at normal pressure to prevent the water from evaporating, and aged at 20-30 °C for 24 h. The precipitate was separated by filtration, and washed alternately with 50.0 ml of anhydrous ethanol and 50.0 ml of deionized water, and centrifuged. The alternating washing was repeated 3 times, and dried at 80 °C for 24 h, and then heated to 200 °C at a heating rate of 5 °C / min at room temperature, and calcined in air for 2 h to obtain g-C3N4 / (Ca 9.4 Fe 0.1 Ag 0.5 )(PO4)6(OH)2 composite powder.
[0030] Example 4
[0031] g-C3N4 / (Ca 9.2 Fe 0.3 Ag0.5 )(PO4)6(OH)2 (wherein the content of g-C3N4 is 20%) composite powder
[0032] 12.5 ml of 0.1 M Fe(NO3)3 solution, 6.3 ml of 0.2 M AgNO3 solution and 47.0 mL of 0.5 M Ca(NO3)2 solution were respectively taken and mixed with 1.2 g of g-C3N4 and ultrasonically treated for 20 min, and then stirred at 95 °C for 1 h. Subsequently, 50.0 mL of 0.3 M NH4H2PO4 solution was added, and the pH value was adjusted to 10-11 by dropping NH3·H2O. The mixture was stirred for 1 h at room temperature to obtain a mixed solution A. The mixed solution A was sealed at normal pressure to prevent the water from evaporating, and aged at 20-30 °C for 24 h. The precipitate was separated by filtration, and washed alternately with 50.0 mL of anhydrous ethanol and 50.0 mL of deionized water, and centrifuged. The alternating washing was repeated 3 times, and dried at 80 °C for 24 h, and then heated to 200 °C at a heating rate of 5 °C / min at room temperature, and calcined in air for 2 h to obtain g-C3N4 / (Ca 9.2 Fe 0.3 Ag 0.5 )(PO4)6(OH)2 composite powder.
[0033] Example 5
[0034] g-C3N4 / (Ca 9.2 Fe 0.3 Ag 0.5 )(PO4)6(OH)2 (wherein the content of g-C3N4 is 30%) composite powder
[0035] 12.5 ml of 0.1 M Fe(NO3)3 solution, 6.3 ml of 0.2 M AgNO3 solution and 47.0 ml of 0.5 M Ca(NO3)2 solution were respectively taken and mixed with 1.9 g g-C3N4 and ultrasonically treated for 20 min, and then stirred at 95 °C for 1 h. Subsequently, 50.0 ml of 0.3 M NH4H2PO4 solution was added, and the pH value was adjusted to 10-11 by dropping NH3·H2O. The mixture was stirred for 1 h at room temperature to obtain a mixed solution A. The mixed solution A was sealed at normal pressure to prevent the water from evaporating, and aged at 20-30 °C for 24 h. The precipitate was separated by filtration, and washed alternately with 50.0 ml of anhydrous ethanol and 50.0 ml of deionized water, and centrifuged. The alternating washing was repeated 3 times, and dried at 80 °C for 24 h, and then heated to 200 °C at room temperature at a heating rate of 5 °C / min, and calcined in air for 2 h to obtain g-C3N4 / (Ca 9.2 Fe 0.3 Ag 0.5 )(PO4)6(OH)2 composite powder.
[0036] Example 6
[0037] g-C3N4 / (Ca 9.2 Fe 0.3 Ag 0.5 )(PO4)6(OH)2 (wherein the content of g-C3N4 is 40%) composite powder
[0038] 12.5 ml of 0.1 M Fe(NO3)3 solution, 6.3 ml of 0.2 M AgNO3 solution and 47.0 ml of 0.5 M Ca(NO3)2 solution were respectively taken and mixed with 2.8 g of g-C3N4 and ultrasonically treated for 20 min, and then stirred at 95 °C for 1 h. Subsequently, 50.0 ml of 0.3 M NH4H2PO4 solution was added, and the pH value was adjusted to 10-11 by dropping NH3·H2O. The mixture was stirred for 1 h at room temperature to obtain a mixed solution A. The mixed solution A was sealed at normal pressure to prevent the water from evaporating, and aged at 20-30 °C for 24 h. The precipitate was separated by filtration, and washed alternately with 50.0 ml of anhydrous ethanol and 50.0 ml of deionized water, and centrifuged. The alternating washing was repeated 3 times, and dried at 80 °C for 24 h, and then heated to 200 °C at a heating rate of 5 °C / min at room temperature, and calcined in air for 2 h to obtain g-C3N4 / (Ca 9.2 Fe 0.3 Ag 0.5 )(PO4)6(OH)2 composite powder.
[0039] Taking Example 6 as an example, Figure 1 This is the UV-DRS spectrum of the sample. It can be seen that the material has a strong absorption effect on light with a wavelength of 220-430nm.
[0040] Figure 2 This is a photo of the antibacterial ring of the sample. It can be seen that the material has a good antibacterial effect on Escherichia coli and Staphylococcus aureus.
Claims
1. A composite powder for sunscreen with antibacterial function, characterized in that: The composite powder is composed of g-C3N4 and iron-silver co-doped hydroxyapatite, and its chemical composition is expressed as g-C3N4 / (Ca 10-x-y Fe x Ag y )(PO4)6(OH)2, wherein 0.1≤x≤1, 0.1≤y≤1, and the mass ratio of g-C3N4 in the composite powder is 20% to 40% of the total mass.
2. The composite powder for sunscreen with antibacterial function according to claim 1, characterized in that: The Fe-Ag co-doped part of the Ca in the hydroxyapatite lattice 2+ Fe 3+ 、Ag + Replace respectively.
3. The composite powder for sunscreen with antibacterial function according to claim 1, characterized in that: The composite powder has strong absorption of light in the wavelength range of 220-430nm, and has a good antibacterial effect on Staphylococcus aureus and Escherichia coli. The color of the composite powder is close to the natural skin color of Asians.
4. A sunscreen composite powder with antibacterial function according to claim 1, wherein the doping element range of the iron-silver co-doped hydroxyapatite is preferably in the general composition formula of x=0.5, y=0.5; the selected mass ratio of g-C3N4 in the composite powder is 30%, and the preferred composite powder has the strongest absorption effect on light in the wavelength range of 220-430nm, retains good antibacterial effects on Staphylococcus aureus and Escherichia coli, has a color close to the natural skin color of Asians, and has the best comprehensive performance.
Citation Information
Patent Citations
Trivalent manganese ion doped hydroxyapatite material as well as preparation method and application thereof
CN112062114A
Sunscreen compound as well as preparation method and application thereof
CN114404314A
Preparation method and application of one-step synthesized Fe-doped hydroxyapatite
CN114681615A
Hydroxyapatite powder with double functions of ultraviolet absorption and antibiosis
CN117208871A